Đạo hàm của hàm số $\Large y=(x^2-2x+3)^{\dfrac{4}{3}}$ là: A. $\Large

Đạo hàm của hàm số $\Large y=(x^2-2x+3)^{\dfrac{4}{3}}$ là: A. $\Large

4.1/5

Tác giả: Thầy Tùng

Đăng ngày: 18 Aug 2022

Lưu về Facebook:

Câu hỏi:

Đạo hàm của hàm số $\Large y=(x^2-2x+3)^{\dfrac{4}{3}}$ là: 

Đáp án án đúng là: D

Lời giải chi tiết:

Chọn D

$\Large y'=\dfrac{4}{3}(x^2-2x+3)^{\dfrac{1}{3}}.(x^2-2x+3)'$ $\Large  = \frac{4}{3}\left( {2x - 2} \right){\left( {{x^2} - 2x + 3} \right)^{\frac{1}{3}}}$ $\Large =\dfrac{8}{3}(x-1)(x^2-2x+3)^{\dfrac{1}{3}}$